Volcanic and igneous plumbing systems understanding magma transport, storage, and evolution in the earth's crust - Burchardt, Steffi (Elsevier, 2018)
Volcanic and Igneous Plumbing Systems: Understanding Magma Transport, Storage, and Evolution in the Earth's Crust synthesizes research from various geoscience disciplines to examine volcanic and igneous plumbing systems (VIPS) in-depth. VIPS comprise a network of magma transport and storage features in the Earth’s crust. These features include dykes, sills and larger magma bodies that form the pathway and supply system of magma beneath active volcanoes. Combining basic principles with world-class research and informative illustrations, this unique reference presents a holistic view of each topic covered, including magma transport, magma chambers, tectonics and volcanism. Addressing a variety of approaches to these topics, this book offers researchers and academics in the Earth Science fields, such as geophysics, volcanology and igneous petrology the information they need to apply the information to their own disciplines.--Provided by publisher.